2016
DOI: 10.1177/1938640016656783
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Distraction Arthrodesis with Fresh Frozen Femoral Neck Allograft

Abstract: Therapeutic, Level IV: Case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Anterograde fixation was also utilized by Amendola et al 3 with no reported cases of hardware removal. Most recently, Monaco et al 24 described the use of partially threaded, headless, cannulated positional screws and emphasized the importance of placement in the nonweightbearing area of heel.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Anterograde fixation was also utilized by Amendola et al 3 with no reported cases of hardware removal. Most recently, Monaco et al 24 described the use of partially threaded, headless, cannulated positional screws and emphasized the importance of placement in the nonweightbearing area of heel.…”
Section: Resultsmentioning
confidence: 99%
“…Tricortical autologous iliac crest bone graft is the most common graft used in SDA. Other graft types used include local autograft from the lateral calcaneal wall exostectomy, 2,12,17,27,29 femoral head allograft, 10,18,22,24,32 iliac crest allograft, 22,27 freeze-dried bovine xenograft, 19 and porous tantalum. 26 Most commonly described is a trapezoid or wedge-shaped bone block with the graft tallest medially and posteriorly (laterally and anteriorly tapered) 3,9,18,25 to prevent the complication of varus malpositioning.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations